ALTERNATIVE FUNDING STRATEGIES FOR REPOSITIONING TECHNOLOGY EDUCATION FOR SUSTAINABLE SKILL DEVELOPMENT AND ECONOMIC DEVELOPMENT IN SOUTH-EAST STATES OF NIGERIA (NAU Journal of Technology and Vocational Education, 2024)
Funding tertiary education in Nigeria has been a challenge bedeviling the quality ofeducation offered in this country. It seems that the government can no longer fundtechnology education adequately to provide the desired skills development trainingneeded for sustainable economic development. The study focused on determining thealternative funding strategies for repositioning technology education for sustainableskills development and economic development in South-East Nigeria. Two researchquestions guided the study and two null hypotheses that were tested at 0.05 level ofsignificance. Survey research design was adopted. The area covered was the fivestates in the South East. The population of the study was 112 respondents (lecturers oftechnical education in tertiary institutions in South East). Structured questionnairewith 20 items which was validated by three experts was used for data collection. Thereliability of the instrument was determined with the measure of internal consistencymethod and the analysis of data with Cronbach Alpha reliability yielded a reliabilitycoefficient of 0.86.Mean and standard deviation was used to answer the researchquestions while t-test was used to test the null hypotheses. Findings showed that therespondents agreed with all the alternative funding strategies listed. There was nosignificant difference between the mean rating of the respondents in federal and statetertiary institutions on the alternative funding strategies. Based on the findingsconclusion was made and it was recommended that institution management shouldrestructure technology education workshops to a mini industry in order to generatefunds, technology education lecturers should attract grants and patronage forresearch and innovations while government should encourage non-governmentalorganisations to support technology education through monetary and non-monetaryinterventions among others.
Keywords: Technology education, funding, alternative funding strategies, skill development, economic development.